PENGEMBANGAN E-BAHAN AJAR BERBASIS CERITA BERGAMBAR TEMA HIDUP BERSIH DAN SEHAT PADA KELAS II SEKOLAH DASAR - Hanum Fatmawati; Nana Hendracipta; Encep Andriana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The learning process explains the materials based on basic competencies and relates to the development and use of learning media. The media is used as input for educators to make it easier for students to achieve learning and make them enthusiastic in learning to facilitate students' understanding of learning. This study aimed to develop e-learning materials based on picture stories for grade II of Elementary School on the theme of Clean and Healthy Living, the sub-theme of Clean and Healthy Living at Home. This study was development research that used the Borg and Gall model modified by Sugiyono's six steps of the development design. The study involved teachers and the second-grade students of SDN Banjarsari. Two students were involved in the individual small group trial, ten students particisated in the first session trial, and ten students were included in the 2nd session trial. The trial results obtained a very high level of feasibility of the teaching materials. The results indicated that the validity of materials from media expert 1 was 88%, and media expert 2 was 93%. Then, the validity result fro